How Should Credit Gaps Be Measured? : An Application to European Countries - Baba, Chikako (IMF Working Papers; Working Paper ;, 2020)
Assessing when credit is excessive is important to understand macro-financial vulnerabilities and guide macroprudential policy. The Basel Credit Gap (BCG) - the deviation of the credit-to-GDP ratio from its long-term trend estimated with a one-sided Hodrick-Prescott (HP) filter-is the indicator preferred by the Basel Committee because of its good performance as an early warning of banking crises. However, for a number of European countries this indicator implausibly suggests that credit should go back to its level at the peak of the boom after the credit cycle turns, resulting in large negative gaps that might delay the activation of macroprudential policies. We explore two different approaches-a multivariate filter based on economic theory and a fundamentals-based panel regression. Each approach has pros and cons, but they both provide a useful complement to the BCG in assessing macro-financial vulnerabilities in Europe.